Non-invasive assessment of liver changes in Eisenmenger patients. (15th December 2017) - Mebus, Siegrun; Nagdyman, Nicole; Kügel, Johanna; Zachoval, Reinhart; Braun, Siegmund Lorenz; Haverkämper, Guido; Opgen-Rhein, Bernd; Berger, Felix; Horster, Sophia; Schoetzau, Jörg; Salvador, Claudia Pujol; Bauer, Ulrike; et al.
Abstract: Background: Eisenmenger syndrome as a severe form of cyanotic congenital heart disease results in a complex multisystemic disorder. Due to increased systemic venous pressure and the inability to ensure systemic perfusion and metabolic requirements, the liver may develop congestion, fibrosis or cirrhosis. This study aimed to assess hepatic abnormalities in Eisenmenger patients non-invasively. Methods and results: 10 adults with Eisenmenger syndrome (six female; median age 44.2 years; range 23–62 years) were enrolled and hepatic involvement was assessed - using clinical assessment, laboratory analysis, hepatic fibrotic markers, abdominal sonography and liver stiffness measurements (transient elastography (TE) and acoustic radiation force impulse imaging (ARFI)). Using imaging and laboratory analysis, 60% (6/10) of the Eisenmenger patients had signs of liver fibrosis (5/10) or cirrhosis (1/10). While TE, however, showed no relevant liver abnormalities in any Eisenmenger patient, ARFI detected liver fibrosis in 5/10 and cirrhosis and 1/10 patients. Conclusions: Adult Eisenmenger patients are at increased risk of hepatic impairment. Non-invasive screening could be helpful in detecting liver alterations. In our small series, however, TE could not detect fibrosis or cirrhosis in any affected patient, while ARFI was very reliable. Patients should be transferred to centres, where a multidisciplinary expert knowledge is available and a close collaboration between cardiologists and hepatologists exists.